Advaita, Christianity and the third space: Abhishiktananda and Bede Griffiths in India - Smith, Jonathan Gordon (Peter Lang, 2020)
"This book examines the space of meeting between two religions that open up when there are honest attempts at interreligious learning. Taking Abhishiktananda and Bede Griffiths as examplars, and the meeting between Advaita Vedanta and Christianity, the nature of the theological movements within this 'Third Space' are identified, and the resultant hybridities are assessed for their relevance to each tradition. After brief biographical sketches, the author considers how these two monks related to the Indian space and the background of colonial history, and then proceeds to use comparative theology and postcolonial theory to examine their theology. Third Space Theory provides insights into the process of hybridization that is taking place, leading to an appreciation of the importance and challenge in the modern world of Third Spaces of meeting"--